2011
DOI: 10.4196/kjpp.2011.15.6.327
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Opium Treatment Can Differentially Induce Brain and Liver Cells Apoptosis in Diabetic and Non-diabetic Male and Female Rats

Abstract: It has been shown that some opium derivatives promote cell death via apoptosis. This study was designed to examine the influence of opium addiction on brain and liver cells apoptosis in male and female diabetic and non-diabetic Wistar rats. This experimental study was performed on normal, opium-addicted, diabetic and diabetic opium-addicted male and female rats. Apoptosis was evaluated by TUNEL and DNA fragmentation assays. Results of this study showed that apoptosis in opium-addicted and diabetic opium-addict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…Asiabanha et al. () examined the influence of opium exposure by i.p. on brain and liver cells apoptosis in male and female diabetic and non‐diabetic rats.…”
Section: Assessmentmentioning
confidence: 99%
“…Asiabanha et al. () examined the influence of opium exposure by i.p. on brain and liver cells apoptosis in male and female diabetic and non‐diabetic rats.…”
Section: Assessmentmentioning
confidence: 99%
“…The results of this study demonstrated improved analgesic effects of intravenous patient controlled analgesia with ketamine on postoperative pain in opium abusers. The effects of chronic opium abuse in altering the threshold of pain tolerance have previously been studied in a number of studies since the issue became a high priority in acute pain research ( 2 , 4 , 6 , 7 , 28 - 32 ). On the other hand, among this large list, there are not many studies that have assessed the effects of ketamine in postoperative pain suppression in these patients ( 17 , 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The withdrawal signs in opium-dependent rats were detected from the 5th day of opium injection. These signs which were occasionally studied for a short duration previous to the next injection were wet-dog shakes as the first sign, and then head shakes, irritability, hyperactivity, ptosis, and writhing ( 6 ). Immediately after the rats were killed, the ovaries were removed and embedded in 0.1 M phosphate-buffered saline (PBS) at pH 7.4 containing 3.7% paraformaldehyde for 30 minutes at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The tissues were then transferred to xylenes and were rinsed twice for 1 hour. Tissues were fixed in molten paraffin wax (58 ºC) for 1 hour, and were then embedded again by fresh paraffin wax ( 6 ). The apoptotic nuclei DNA fragmentation was assessed by the TUNEL technique using the in situ cell death detection kit based on the manufacturer’s kit manual that has been described previously ( 6 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation